Evaluation of an interprofessional education program involving medical and pharmacy students: a mixed-method study - Josephine F. Mertens; Marleen H. M. Hessel; Thomas G. H. Kempen; Stefan Böhringer; Adriaan F. Norbart; Chris W. Walinga; Teun van Gelder (BMC Medical Education)
Abstract Background Effective pharmacotherapy requires strong collaboration between physicians and pharmacists, highlighting the need for interprofessional education (IPE) in university curricula. This study evaluated the impact of an IPE program on medical and pharmacy students, focusing on their perceived development of interprofessional collaborative competencies, perceived learning outcomes, and clinical collaboration perceptions. Methods A mixed-method approach was employed to evaluate an IPE program that consisted of three mandatory activities with increased complexity and autonomy, that were integrated into the medical and pharmacy students’ curricula. From September 2022 to June 2023, using a retrospective pre-post approach, students rated their competence levels after an educational activity using the Interprofessional Collaborative Competency Attainment Scale (ICCAS). The participants also answered open-ended survey questions about their learning outcomes. Medical students participated in both uniprofessional education (UPE) and IPE, while pharmacy students participated exclusively in IPE. Effect sizes for competency development were estimated, and subgroup analyses were performed to examine the impact of multiple IPE activities. Semi-structured interviews provided additional qualitative insights, which were analyzed using thematic analysis. Results Of the 309 surveys completed (response rate 64%, with 274 medical and 35 pharmacy students), all 21 ICCAS items showed statistically significant improvement in both UPE (n = 127) and IPE (n = 182) (p < 0.05). While effect sizes for UPE were small across all items, IPE had medium effect sizes for six items and large effect sizes for two items. Overall, students rated themselves as more capable of interprofessional collaboration after IPE, with 55% (n = 124) reporting feeling 'somewhat better' and 6% (n = 14) feeling 'much better,' compared to 16% (n = 12) and 0%, respectively, after UPE. Competency development seems to improve slightly with an increased number of IPE activities. Pharmacy students reported somewhat higher post-activity scores than medical students did. Qualitative data from open-ended survey responses and interviews with six medical students and four pharmacy students highlighted a deeper understanding of professional roles and a greater appreciation for collaborative work through this program. Conclusions This IPE program focused on pharmacotherapy improved self-perceived interprofessional collaborative competencies among medical and pharmacy students. Through multiple interprofessional activities, students can develop a deeper understanding of professional roles and improve collaborative skills.